Solar Panel Colling System Design Using Solid Hydrate Salt - Dwiputra, Muhammad Farhan; Asri, Asri; Hasibuan, Arnawan; Jannah, Misbahul; Ezwarsyah, Ezwarsyah; Asran, Asran (Indonesian Scientific Journal, 2024)
Solar energy is an alternative energy that is abundant, renewable, and does not produce greenhouse gas emissions, so it has the potential to be developed into energy to replace fossil energy as a source of electricity generation. The main technology in the utilization of solar energy is solar panels, solar panels consist of solar cells made of semiconductor materials, such as silicon. These solar cells convert photon energy from sunlight into electrical energy through the photovoltaic effect. Changes in the temperature of solar cells are affected by the ambient temperature, clouds, and wind speed where the solar panel is placed. Very high air temperatures can affect the performance of solar panels where the optimal temperature of solar panels is 25°C, any increase in ambient temperature can reduce the output power and also the output voltage on solar panels. This research focuses on analyzing a solar panel cooling system that combines the use of solid salt hydrate and heatsinks. Solid salt hydrate has the ability to absorb heat as it melts, making it an effective cooling material. Meanwhile, the heatsink plays a role in enhancing heat transfer from the solar panel to the surrounding environment. The combination of solid salt hydrate and heatsink is expected to provide a solar panel cooling solution that is not only effective and efficient, but also environmentally friendly. By using these two components, this research is expected to contribute to the development of more efficient and sustainable solar panel technology. In addition, the results of this research also aim to provide optimal solar panel cooling system design recommendations for various environmental conditions, so as to improve the performance and longevity of solar panels002E